IMPLEMENTASI PACKAGING STRATEGY GUNA MENINGKATKAN DAYA SAING USAHA RENGGINANG BERBAHAN BAKU UBI DI DESA TOAPAYA UTARA - Anggia Sekar Putri ,; Yuritanto, Yuritanto; Yusrizal, Yusrizal; Nanda Dewi Anggraeni ,; Ida Jernita Zendrato,; Nanang Willy Prayogo ,; Rara Christya Marshanda ,; Ramadi, Ramadi; Rega Andira Pratama , (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The rengginang business made from cassava in TOAPAYA UTARA Village District is generally considered a medium, small and micro enterprise (MSME) which has weaknesses in terms of business management, especially strategic marketing management, this condition is relatively seen as an obstacle to business competitiveness. Packaging is the activity of designing and producing containers or wrappers as a product. The aim of a packaging strategy is to produce packaging that is attractive, easy to carry, safe, does not cause food contamination, and provides complete and adequate product information. Good packaging can increase sales of a product. This Community Service uses the coaching clinic method, which is a combination of three indicators (counseling, mentoring and evaluation). The result of this research is that the implementation of a packaging strategy can increase the competitiveness of product sales. Good packaging is a means of communication that helps increase sales. Over time, packaging has undergone an evolution in its function, from initially only aiming to protect a product, now having a broader function, one of which is branding or product identity. The best local products are produced, in this case rengginang which has the potential to be absorbed in the market. Packaging Strategy formulation is effective in terms of: choosing colors that are attractive and inviting attention, having distinctive characteristics, containing information about rengginang products made from sweet potatoes, providing comfort for consumers who see it, giving a more positive impression and providing relatively high emotional power, and implementing business management good by partners.